THE EFFECT OF RHIZOBIUM SEED INOCULATION ON YIELDS AND QUALITY OF FORAGE AND SEED OF BERSEEM CLOVER (TRIFOLIUM ALEXANDRINUM L.) AND ITS IMPACT ON SOIL FERTILITY AND SMALLHOLDER FARMER’S INCOME - M.S. Tufail; G.L. Krebs; J. Ahmad; A. Southwell; J.W. Piltz; P.C. Wynn (Journal of Animal and Plant Sciences, 2018)
Afield experiment was conducted to investigate the effects of Rhizobium seed inoculation on forage and seed yield components and the forage quality of berseem clover (Trifolium alexandrinum). The experiment comprised of two treatments, seed inoculation with Rhizobium trifolii and the non-inoculation (control). The results revealed that the seed 2 inoculation significantly affected (P<0.005) and produced maximum number of stems/m (348.2), plant height (24.4cm), 2 green forage yield (39.9 t/ha), dry matter yield (5.54 t/ha), number of heads per m (339), number of seeds per head (24.5), 1000-seed weight (3.851 g) and predicted seed yield (320 kg/ha) as compared to non-inoculated plots. The similar trend of results was also found in the forage quality parameters and seed inoculation produced maximum values of neutral detergent fiber (26.5%), crude protein (28.6%) and water soluble carbohydrates (2.02%). However, the acid detergent fiber (21.0%) and metabolisable energy (10.7%) were found to benon-significant. The use of Rhizobium inoculum also added available nitrogen (N) to soil after the crop increasing available N to0.0414% as compared to 0.0283% in thenon-inoculatedcontrol. The use of Rhizobium trifolii inoculum in combination with the improved variety Agaitti Berseem-2002, produced an additional net income of PKR 111,913 Rs/ha (US$ 1145/ha) compared to non- inoculated plots. farmers. improvements to berseem clover forage production from
Keywords: Forage development; forage quality; poverty alleviation; rural development; seed production; smallholder